Mental health literacy in nursing students: Insights from a cross-sectional analysis - Mohamad AlMekkawi; Rouwida ElKhalil; Annie Rosita Arul Raj; Ibrahim Bashayreh; Iffat Elbarazi; Mohammed Al Maqbali; Ciara Hughes (PLoS ONE, 2025)
Mental health literacy is crucial for nursing students to deliver effective patient care; however, its development throughout their academic journey remains underexplored. This study aimed to assess mental health literacy among nursing students in the UAE and examine factors influencing their literacy levels. A quantitative cross-sectional study was conducted from February 2024 to August 2024 using convenience sampling. A total of 295 undergraduate nursing students participated in the study. Data were collected using the Mental Health Literacy Questionnaire (MHLq) and analyzed using SPSS software (version 24). Descriptive and inferential analyses were conducted to calculate means, standard deviations, percentages, and measures of association using t-tests for students’ sociodemographic variables, dimensions, and global scores, with a significance level of 0.05 for the tests. The findings indicated that participants (all female, with a mean age of 20.7 ± 1.85 years) had a mean MHLq score of 108.19 ± 10.53. Fourth-year students scored higher (110.78 ± 9.79) than lower-year students (106.85 ± 10.68). Students with family or friends who were affected had higher scores (48.00 ± 6.16) than those without (45.97 ± 6.16). The highest-scoring domain was knowledge of mental health problems (46.59 ± 6.40), while self-help strategies scored lowest (16.99 ± 2.61). Students with a personal history of mental illness had lower scores. The study also indicated a statistically significant association between students’ marital status, their level of study, and their first-aid skills and help-seeking behavior. The study highlights the importance of integrating mental health literacy into undergraduate nursing curricula to enhance student’s ability to provide patient-centered care for individuals with mental health disorders. Implementing targeted educational strategies focusing on awareness, recognition, and communication may strengthen students’ competency and preparedness for mental health care practice.